PORE PRESSURE ESTIMATION IN HARD UNLOADING-OVERPRESSURE ZONE USING SINGLE COMPACTION EQUATION, CASE STUDY: LOWER KUTAI BASIN - Irawan Y Tribuana; Usep Mulyadi; Agus M Ramdhan; Asep H Rustam (Scientific Contributions Oil and Gas, 2016)
Pore pressure estimation in hard-overpressure zone is very important in drilling activities. Correct and precise estimation are able to reduce the cost for drilling due to reduced non-productive time (NPT) and in increase in safety aspect while drilling. Pore pressure estimation is done by post-mortem analysis in exploration wells using validation points from pressure measurement data such as Drill Stem Testing (DST), Modular Dynamic Tester (MDT), and Repeat Formation Tester (RFT). A wireline logs data used for identification of the type of overpressure and predicts pore pressure magnitude in the shale section. Through the correlation between effective-stress and velocity, a single compaction equation was obtained for the Lower Kutai Basin with the value of : 5.097 * σ 0.854. By using this single equation, pre-drill pore pressure prediction activity will be more easy and could estimate pore pressure in hard-overpressure zone precisesly.